Retrospective Analysis of Postgraduate Theses in Nursing and Business Administration on Employee Empowerment in Turkey - Şehriban Serbest; Aytolan Yıldırım (Association of Nurse Managers, 2023)
Aim: The aim of this study is to examine the characteristics of postgraduate theses in the field of nursing and business administration on employee empowerment in Turkey. Method: A total of 202 postgraduate theses, 19 in the field of nursing and 183 in the field of business administration, which were registered in the National Thesis Center between 1997-2021 and met the inclusion criteria, were examined using the data collection form prepared by the researchers and evaluated using descriptive statistics. Results: Within the scope of the review, it was determined that most of the theses examined in the field of nursing and business administration were master's theses, the number of samples was higher in the field of nursing than the business administration, the Structural Empowerment Scale was the most common data collection tool in the field of nursing, and the Psychological Empowerment Scale in the field of business administration. In the field of nursing, it was determined that empowerment was mostly discussed in relation to employee performance and organizational performance, work environment characteristics, leader behaviors, and employee turnover and retention, while in the field of business, organizational commitment, organizational identification, trust, work environment characteristics, transformational leadership, and human resource management are discussed. Conclusion: It was concluded that the number of samples was higher in the field of nursing, the structural dimension of empowerment was the most common subject, and nurse empowerment was associated with the needs of the nurses. It is recommended to use qualitative research methods that will provide an in-depth examination of employee empowerment in theses, to examine the psychological dimension of empowerment in the field of nursing, and to address the factors related to employee empowerment.